"WHOEVER ISN'T FOR US IS AGAINST US IN THIS CASE": THE ROLE OF CONTEXTUALIZATION IN SEAMUS HEANEY'S THE BURIAL AT THEBES - Rosa, Janaina Mirian (Revista X, 2020)
The aim of this article is to discuss the issue of contextualization in Seamus Heaney’s translation of Sophocles’ Antigone, entitled The Burial at Thebes, in relation to the invasion of Iraq by the United States government in 2003. Such a subject served as an inspiration for the translator in the composition of his work. For the purpose of this study, specific passages in the play were selected in order to examine the lines of some of the characters in comparison to public speeches of former American President George W. Bush, as well as Bush’s decisions during his government. The treatment of prisoners in war situations during Bush’s presidency is also highlighted in the article. Heaney’s The Burial at Thebes brings a critical viewpoint concerning contemporary matters, as the similarities regarding the subject of power abuse in both Creon’s and Bush’s governments can be attentively observed.